A lowermost Ordovician tabulate-like coralomorph from the Precordillera of western Argentina: a main component of a reef-framework consortium. (21st December 2016) - Carrera, Marcelo G.; Astini, Ricardo A.; Gomez, Fernando J.
Abstract: Although putative corals of uncertain affinities occur in the early Cambrian, the earliest definite tabulate corals have not been described prior to the Early Ordovician in North America. This paper reports a new finding of a tabulate-like coralomorph forming part of biostratigraphically well-constrained reef mounds in the latest Cambrian– Early Ordovician La Silla Formation in the Argentine Precordillera. The oldest record of the coralomorph genus Amsassia is reported and a new species, A . argentina, is erected. The discovery of this genus in the lowermost Ordovician modifies the previously proposed paleogeographic distribution and patterns of origination and migration routes of this coral-like organism. Amsassia argentina n. sp. constitutes a main framework builder together with a complex microbial consortium. This oldest occurrence of Amsassia as a reef builder represents a new record of a skeletal organism in the gap of metazoan reef constructors after the demise of archaeocyaths in the late early Cambrian.